The clinical interpretation and significance of electronic fetal heart rate patterns 2 h before delivery: an institutional observational study. - Maso, Gianpaolo; Businelli, Caterina; Piccoli, Monica; Montico, Marcella; De Seta, Francesco; Sartore, Andrea; Alberico, Salvatore (Arch Gynecol Obstet, 2012)
PURPOSE: To evaluate the clinical significance of intrapartum fetal heart rate (FHR) monitoring in low-risk pregnancies according to guidelines and specific patterns. METHODS: An obstetrician, blinded to neonatal outcome, retrospectively reviewed 198 low-risk cases that underwent continuous electronic fetal monitoring (EFM) during the last 2 h before delivery. The tracings were interpreted as normal, suspicious or pathological, according to specific guidelines of EFM and by grouping the different FHR patterns considering baseline, variability, presence of decelerations and bradycardia. The EFM groups and the different FHR-subgroups were associated with neonatal acid base status at birth, as well as the short-term neonatal composite outcome. Comparisons between groups were performed with Kruskal-Wallis test. Differences among categorical variables were evaluated using Fisher's exact test. Significance was set at p < 0.05 level. RESULTS: Significant differences were found for mean pH values in the three EFM groups, with a significant trend from "normal" [pH 7.25, 95 % confidence interval (CI) 7.28-7.32] to "pathological" tracings (pH 7.20, 95 % CI 7.17-7.13). Also the rates of adverse composite neonatal outcome were statistically different between the two groups (p < 0.005). Among the different FHR patterns, tracings with atypical variable decelerations and severe bradycardia were more frequently associated with adverse neonatal composite outcome (11.1 and 26.7 %, respectively). However, statistically significant differences were only observed between the subgroups with normal tracings and bradycardia. CONCLUSIONS: In low-risk pregnancies, there is a significant association between neonatal outcome and EFM classification. However, within abnormal tracings, neonatal outcome might differ according to specific FHR pattern.
Keywords: Acidosis; Bradycardia; Female; Fetal Blood; Fetal Monitoring; Heart Rate, Fetal; Humans; Hydrogen-Ion Concentration; Infant, Newborn; Labor, Obstetric; Predictive Value of Tests; Pregnancy; Pregnancy Outcome; Retrospective Studies; Single-Blind Method; Statistics, Nonparametric; Time Factors